Detection and quantification of entanglement with measurement-device-independent and universal entanglement witness - Ke,Z-J; Wang,Y-T; Yu,S; Liu,W; Meng,Y; Li,Z-P; Wang,H; Li,Q; Xu,J-S; Xiao,Y; Tang,J-S; Li,C-F; et al. (Chinese Physics B, 2020)
Entanglement is the key resource in quantum information processing, and an entanglement witness (EW) is designed to detect whether a quantum system has any entanglement. However, prior knowledge of the target states should be known first to design a suitable EW, which weakens this method. Nevertheless, a recent theory shows that it is possible to design a universal entanglement witness (UEW) to detect negative-partial-transpose (NPT) entanglement in unknown bipartite states with measurement-device-independent (MDI) characteristic. The outcome of a UEW can also be upgraded to be an entanglement measure. In this study, we experimentally design and realize an MDI UEW for two-qubit entangled states. All of the tested states are well-detected without any prior knowledge. We also show that it is able to quantify entanglement by comparing it with concurrence estimated through state tomography. The relation between them is also revealed. The entire experimental framework ensures that the UEW is MDI.